2013
DOI: 10.1002/dc.23029
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ProExC and IMP3 immunocytochemical staining in atypical glandular cells of undetermined significance in liquid‐based cervical cytology

Abstract: The diagnosis of atypical glandular cells of undetermined significance (AGUS) in liquid-based cervical cytology specimens shows significant underlying pathology in only 30% of cases, while the remaining cases are found to be benign (reactive, reparative/metaplastic). Previous studies have reported positive ProExC and IMP3 staining in neoplastic glandular lesions of the uterine cervix and corpus. We present our experience with the utility of these markers in the evaluation of AGUS cases in liquid-based cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In our study, using both markers enabled identification of cellular abnormalities in four of five ASC-US samples, corroborating the results of previous studies focused on atypical squamous cell cytology [ 5 , 8 , 27 , 31 ]. We also identified structural modifications in samples with cytological abnormalities without HPV-DNA identification.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, using both markers enabled identification of cellular abnormalities in four of five ASC-US samples, corroborating the results of previous studies focused on atypical squamous cell cytology [ 5 , 8 , 27 , 31 ]. We also identified structural modifications in samples with cytological abnormalities without HPV-DNA identification.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in the setting of differentiating glandular neoplasms from squamous lesions, the performance of ProEx C appears to be suboptimal for that positivity percent showed no statistically significant difference in both lesion subgroups. Therefore, Ricardo et al used IMP3/ProEx C staining to analyze specimens diagnosed as atypical glandular cells of uncertain significance (AGUS) based on cervical cytology and showed that this method generated a positive predictive value of 100% for adenocarcinoma and a negative predictive value of 83% for lesions not associated with adenocytes 55. Hence, it was suggested that IMP3/ProEx C staining may serve as a potential diagnostic marker for patients with AGUS.…”
Section: Exploration Of Other Cytological Markersmentioning
confidence: 99%
“…Therefore, the IGF2BP can be used as a valuable tumor marker in human cancer. However, reports show considerable differences in the expression frequency among different types of cancer [11][12][13][14][15][16][17][18][19][20][21][22][23][24] , which may be due to the speci city of tissues, use of different antibodies, staining schemes, and scoring standards in experiments. Ramaswamy Suhasini suggest that the IGF2BP3 may promote the expression of the target IGF2 mRNA in an mTOR-controlled manner and promote the tumor's growth 25,26 .…”
Section: Introductionmentioning
confidence: 99%